The Ability to Maintain Static Balance in Younger School Children and its Relation to the Stability of a Posturographic Surface - Żurek, Piotr; Rynkiewicz, Mateusz; Wójciak, Piotr; Morawin, Barbara; Rynkiewicz, Tadeusz (Journal of Sports Research, 2015)
Introduction: The ability to maintain one’s balance plays vital role during the activities of daily living. Efficient maintenance of body balance is determined by the number and type of stimuli providing information on a body position. The aim of this study was to analyze the ability to maintain balance in 7- to 12-year-old children. We analyzed the extent and direction of changes in balancing skills related to subject’s age and stability of a posturographic surface. Material and methods: The study included 266 children aged between 7 and 12 years. The level of static balance was determined with a posturographic method, with a child standing with the eyes open, first on a stable, and then on an unstable position. Results: The children aged between 7 and 8 years presented lower levels of static balance. The level of balancing skills turned out to be higher in the case of 9- to 12-year-old children. Reduced stability of a posturographic surface resulted in greater difficulties in maintaining balance. This change was observed regardless of a subject’s age and manifested as an increase in the area developed by the center of pressure and greater variability of both the velocity and number of sways in the sagittal and frontal plane. The change of the posturographic surface into an unstable one resulted in greater instability in both the frontal and sagittal plane. The increase in the area developed by the center of pressure reflected higher velocity and greater number of sways.